Film Pendek KAWA sebagai Medium Penceritaan Dilema Perempuan Minangkabau - Andhika, Yuditia Leo; Angelina, Ayu Mella (Institut Seni Indoensia Surakarta, 2023)
Kawa is a short film that raises the issue of Minangkabau women today in response to the changes in social life of society. The film tells the life of a woman in Minangkabau who has since been inserted the customary order of the sumbang duo baleh in shaping her personality. In the tambo Minangkabau the concept of the sumbang duo baleh is strictly applied to women, and constitute the values of the rules of behavior that are structured for Minangkabau women. The acts and behavior of women in Minangkabau which, when not in accordance with the customary order, will be considered wrong by customary view. As the times progressed, many Minangkabau women wanted to leave their hometown and continue their lives. The film presents the controversy of Minangkabau women who have their own point of view about their cultural reality. The film Kawa tries to capture the dilemma faced by women over the customary rules of Minangkabau. Different aspects of life are restricted so as to narrow the spaces of women's movements and place women on a social construction that raises controversy in living a life between following their desires or obeying customary rules that tend to limit their ideals.